2018
DOI: 10.2320/matertrans.m2017351
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Nickel and Iron from Low-Grade Nickel Laterite Ore via a Solid-State Deoxidization Method Using Methane

Abstract: This work focuses on the solid-state deoxidization of low-grade nickel laterite ore under various conditions using methane. The effects of the reduction temperature, reduction time, and methane concentration on the metallization rates of nickel and iron were investigated. The nickel metallization rate increased as the temperature increased to 600°C; it then decreased as the temperature was further increased. The iron metallization rate increased gradually as the temperature increased. The nickel metallization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 20 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Despite extensive investigations ,,,,,, of NiO reduction by methane, many questions remain about its kinetics and molecular and structural transformation mechanisms. The carbon deposition, however, limits the kinetic measurement of NiO reaction with CH 4 . , Nonisothermal experiments with low heating rates (25 K/min) showed that reduction starts at ∼625 K and the full conversion can be achieved at ∼1000 K, while further heating results in pyrolytic carbon deposition .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite extensive investigations ,,,,,, of NiO reduction by methane, many questions remain about its kinetics and molecular and structural transformation mechanisms. The carbon deposition, however, limits the kinetic measurement of NiO reaction with CH 4 . , Nonisothermal experiments with low heating rates (25 K/min) showed that reduction starts at ∼625 K and the full conversion can be achieved at ∼1000 K, while further heating results in pyrolytic carbon deposition .…”
Section: Introductionmentioning
confidence: 99%
“…19−21 In chemical looping combustion, cyclic oxidation and reduction of Ni-based oxygen carriers are essential for clean power generation with simultaneous separation of CO 2 . 22−30 Despite extensive investigations 5,7,11,27,28,31,32 of NiO reduction by methane, many questions remain about its kinetics and molecular and structural transformation mechanisms. The carbon deposition, however, limits the kinetic measurement of NiO reaction with CH 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has been conducted on the reduction of NiO using CH 4 . ,,,, These works show that pyrolytic carbon forms and deposits on the reduced nickel, creating kinetic limitations. , For example, in nonisothermal conditions, at 350–750 °C, the reduction proceeds without forming pyrolytic carbon, while at 750–1020 °C, rapid decomposition of CH 4 results in significant carbon buildup . The reduction kinetics at these distinctive temperature ranges follow geometrical contraction and nucleation–growth models with calculated activation energies of 103 and 111 kJ/mol, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It has a wide range of applications in the fields of national defense and military industry, chemical industry, metallurgy, aerospace, transportation and new materials. 1,2) According to the statistics of all nickel reserves, 30% exists as sulfide ores with the balance comprised of oxide ores. In nickel production, about 60% of the metal nickel was produced from sulfide ores, and laterite nickel ore only accounts for 40%.…”
Section: Introductionmentioning
confidence: 99%